Determinants and Evaluation of Nasal Airflow Perception - Shen, Jasper; Hur, Kevin; Zhao, Kai; Leopold, Donald A.; Wrobel, Bozena B. (Facial Plastic Surgery, 2017)
The sensation of nasal airflow, or nasal airway patency, is an important consideration in the treatment outcome of nasal airway obstruction. Clinicians striving to optimize the nasal passageway have relied on techniques aimed at decreasing peak airway resistance across nasal valves. Nonetheless, the evaluation of the nasal airway is multifaceted, and the objective determinants of subjective nasal patency remain incompletely elucidated. While rhinomanometry, peak nasal inspiratory airflow, and acoustic rhinometry have traditionally been used in research to focus on resistance as a measure of patency, an emerging body of evidence suggests that subjective nasal patency is more significantly correlated to the dynamic change of nasal mucosal temperature. The objective of this review is to provide the technical background on nasal airflow perception and intranasal trigeminal function as crucial to those performing functional and aesthetic rhinosurgery.
Keywords: nasal obstruction; functional nasal surgery; trigeminal function; mucosal cooling; nasal patency